Leiomyosarcoma: Prognostic outline of a rare head and neck malignancy. (August 2019) - Saluja, Tajindra Singh; Iyer, Janaki; Singh, Satyendra Kumar
Highlights: Clinical outcome of primary IO and EO LMS did not show significant difference. Secondary head-neck LMS carries a dismal prognosis. Adjuvant therapy should be considered irrespective of tumor size. Molecular analysis will help decipher if site of origin determines clinical outcome. Abstract: Soft tissue sarcomas (STS) are mesenchymal malignant neoplasms with a broad spectrum of biologic behaviour. Most STS show predilection for extremities with rarity in head and neck. Leiomyosarcoma (LMS) is an extremely rare STS in head and neck due to the paucity of smooth muscles in this anatomical region. Owing to its rarity, diagnosis of LMS is often delayed or is often misdiagnosed. Our study aimed to evaluate clinico-demographic factors determining clinical course of primary head-neck LMS. Further, we also assessed cases of secondary head-neck LMS and LMS due to other causes to compare their clinical outcome with primary head-neck LMS. In primary LMS cases, intraoral LMS showed slightly better prognosis than extraoral LMS. Survival analysis revealed that prognosis of primary LMS was significantly better than secondary LMS. No significant difference in survival was seen between primary LMS and LMS due to other causes. These observations indicate that site of origin appears to determine the clinical behaviour of LMS. Results showed that size, recurrence and metastasis are important prognostic variables. Though large tumor size was associated with poor prognosis, tumor aggressiveness may not be directly proportional to its size. Surgical management with or without adjuvant therapy was associated with favourable outcome. As several factors are associated with prognostic outcome of head-neck LMS, multimodality therapy approach after careful analysis of various prognostic variables in each case on an individual basis is essential.